2016
DOI: 10.3109/13880209.2015.1107103
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effect of medicinal plants on the contractility of post-hypoxic isolated guinea pig atria – Potential implications for the treatment of ischemic–reperfusion injury

Abstract: Context Ischemic-reperfusion injury is accompanied by a decreased contractility of the myocardium. Positive-inotropic agents have proven useful for treating this condition but may exert serious side-effects. Objective In this study, aqueous preparations from Abelmoschus esculentus L. Moench (Malvaceae), Annona muricata L. (Annonaceae), Bixa orellana L. (Bixaceae), Cecropia peltata L. (Moraceae), Erythrina fusca Lour. (Fabaceae), Psidium guajava L. (Myrtaceae) and Terminalia catappa L. (Combretaceae) were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Of the three studies which investigated A. muricata leaf extract in renal effect, [18,25,29] two studies demonstrated a nephroprotective effect, [18,25] while one demonstrated a nephrotoxic effect [29] with no substantial differences in the dose, formulation or route of administration. There were limited data reported on the cardiac (n = 1), [38] haematological (n = 2) [30,39] and reproductive (n = 1) [26] effect of A. muricata leaf extract.…”
Section: Chemopreventive Potentialmentioning
confidence: 99%
“…Of the three studies which investigated A. muricata leaf extract in renal effect, [18,25,29] two studies demonstrated a nephroprotective effect, [18,25] while one demonstrated a nephrotoxic effect [29] with no substantial differences in the dose, formulation or route of administration. There were limited data reported on the cardiac (n = 1), [38] haematological (n = 2) [30,39] and reproductive (n = 1) [26] effect of A. muricata leaf extract.…”
Section: Chemopreventive Potentialmentioning
confidence: 99%
“…In addition, C. pachystachya also reduced inflammation and renal lesions associated with ACEinhibition, reduction of macrophage infiltration, angiotensin II and c-Jun N-terminal kinase expression, and arginase activity in the renal cortex of rats (Table 5S, Supporting Information) [93,94]. Also, the aqueous extract of the leaves of C. peltata showed a positive inotropic effect on isolated guinea pig atria and caused injury to cardiomyocytes [95].…”
Section: Cardiovascular Effectmentioning
confidence: 89%
“…Through scrutiny of its ethnomedical uses, a wide range of biological activities, including 'antibacterial, antifungal, antioxidant, anti-inflammatory, anti-carcinogenic, enhanced gastrointestinal motility, neuropharmacological, anticonvulsant and antihypercholesterolemic activities have been described in the literature. 19…”
Section: Pharmacological Applicationsmentioning
confidence: 99%